Minority Women, Media, and Body Image - Carolyn L. Martin; Eboni J. Baugh (EDIS)
FCS2301, a 3-page fact sheet by Carolyn L. Martin and Eboni J. Baugh, investigates the myriad effects of media on minority women’s self-perception and body image, as well as provide tips on combating negative imagery so that young women may positively enhance their view of themselves. Includes references. Published by the UF Department of Family Youth and Community Sciences, November 2009.